Methane oxidation to methyl trifluoroacetate by simple anionic palladium catalyst: Comprehensive understanding of K2S2O8-based methane oxidation in CF3CO2H - Cheong, Seok-Hyeon; Kim, Daeun; Dang, Huyen Tran; Kim, Dongwook; Seo, Bora; Cheong, Minserk; Hong, Soon Hyeok; Lee, Hyunjoo (Academic Press, 2022)
The partial oxidation of methane to methyl trifluoroacetate (MeTFA) in trifluoroacetic acid (HTFA) is one of the most selective methane conversion reactions. We report that the simple anionic form of palladium, PdCl(4)(2-)can effectively convert methane to MeTFA compared to neutral PdCl2 in the K2S2O8-HTFA oxidation system. The anionic catalyst form appears to increase the Pd solubility in the polar protic HTFA solvent, thereby facilitating transformation to PdTFA4(2)-which is supposed to be the real catalytic species in this PdCl42-- catalyzed methane oxidation. It was found that not only methane oxidation but also solvent HTFA oxidation proceeded to a substantial degree, which limited the yield of MeTFA by consuming the oxidant, K2S2O8. Furthermore, for the first time, the role of trifluoroacetic anhydride (TFAA) was identified; it removes water produced by KHSO4 and HF, which are the reduced form of K2S2O8 and the oxidation byproduct of HTFA, respectively. The reaction equations for methane to MeTFA, and HTFA to CO(2 )in K2S2O8-HTFA system are suggested. (C) 2022 Elsevier Inc. All rights reserved.